Noticias de arte religioso y vida comunal durante la segunda mitad del siglo XVI en el Memorial de Sololá - Luján Muñoz, Jorge (Revista Española de Antropología Americana, 2003)
A segment at the end of the manuscript known as the Annals of the Kaqchikels, never published nor translated until 1999, provides new data about the construction, between 1584 and 1596, of Solola’s parochial church, the new main reredos, the sculpture of the Virgin of the Assumption, the «monumento» for Good Thursday, the organ, the silver lamp for the Holly Sacrament, and the main bell. All this new information is correlated with other documents and research on colonial art.